Bioactive Compounds of the Stem Bark of Parkia Biglobosa - Chinweizu Ejikeme Udobi, Josiah Ademola Onaolapo (Journal of Applied Pharmaceutical Science)
Phytochemistry, elemental analysis and Infra red spectroscopy were used in combination to confirm the bioactive compounds encountered in the aqueous fraction of the extract of the stem bark of Parkia biglobosa. Bioautography results obtained confirmed the activity of these compounds singly and in combination against Staphylococcus. aureus and Pseudomonas aeruginosa -all organisms of medical and pharmaceutical importance. All results obtained brings us closer to the real identity of these compounds. Work is going on in our laboratory for the structure elucidation of the compounds.
Keywords: Phytochemistry,Bioactive,Parkia biglobosa,Pharmaceutical,Elucidation,Compounds.